Application of shape memory polymers in wettability transition on superomniphobic surfaces - Wang, Wei, author; Salazar, Joshua, author; Vahabi, Hamed, author; Joshi-Imre, Alexandra, author; Voit, Walter E., author; Kota, Arun K., author (Colorado State University. Libraries, 2017)
Superomniphobic surfaces are extremely repellent to virtually all liquids. Prior work have emphasized the importance of low solid surface energy and re-entrant texture (i.e., convex or overhang texture) in the design of superomniphobic surfaces. While superomniphobic surfaces with a wide variety of textures have been reported in literature, to the best of our knowledge, there are no reports of superomniphobic surfaces with metamorphic textures (i.e., textures that transform their morphology in response to an external stimulus). In this work, we present the first-ever metamorphic superomniphobic (MorphS) surfaces fabricated with a thermo-responsive shape memory polymer.
294 - Hamed Vahabi
Keywords: superomniphobic; wettability transition; metamorphic; shape memory polymers